THE WELFARE LEVEL OF FISHERMAN HOUSEHOLD IN MUARA SAKO LANGGAM VILLAGE LANGGAM DISTRICT PELALAWAN REGENCY RIAU PROVINCE - Natalia Kristiani Sianturi; Zulkarnain Zulkarnain; Trisla Warningsih (Berkala Perikanan Terubuk, 2020)
This research was conducted in July 2019 in Muara Sako, Langgam Village, Langgam District, Pelalawan Regency, Riau Province. The method used is a survey method by directly observing the spaciousness by collecting data through interviews based on a questionnaire, the population in this study were fishermen households living in the estuary of sako as many as 62 households. The results showed that 62 Muara Sako fishermen households as many as 46 (74.20%) had dependents ranging from 4-6 people and as many as 16 (25.80) had dependents ranging from 1-3 people, while respondents aged 40-49 were 27 (43.55%) and 42 people (67.74%) had never attended school. Muara Sako fishermen households are included in the category of low welfare level of 38 households (61.29%) and fishermen households included in the category of moderate welfare level are 24 households (38.71%).